Effects of gold, dapsone, and prednisone on serum C-reactive protein and haptoglobin and the erythrocyte sedimentation rate in rheumatoid arthritis. Issue 2 (April 1979) - McConkey, B; Davies, P; Crockson, R A; Crockson, A P; Butler, M; Constable, T J; Amos, R S
Abstract : Sequential measurements of serum C-reactive protein (CRP), serum haptoglobin (Hp), and erythrocyte sedimentation rate (ESR) were made in 209 patients with rheumatoid arthritis (RA); 78 of them were treated with gold, 71 with dapsone, and 60 with prednisone. The results were expressed as proportional changes in the measurements at 28-day intervals after treatment began. The period of study was 140 days. During treatment with gold and dapsone there were statistically significant gradual and progressive falls of similar magnitude in serum CRP and ESR. During treatment with prednisone serum CRP and ESR fell abruptly by 28 days and thereafter altered little. At 140 days prednisone had had the largest proportional effect on both measurements. During gold treatment the fall in serum Hp was similar to that of the ESR. In contrast, prednisone had little effect on Hp levels despite large falls in serum CRP and the ESR. Either prednisone stimulates Hp synthesis or the divergence is an expression of the difference in type of effect between gold and prednisone on RA. The effect of dapsone on serum Hp was large and progressive; it partly reflects haemolysis and, since the haemolysis was not progressive, partly improvement in the RA. The results show the relative efficacy of the drugs and suggest that dapsone may be a useful alternative treatment for RA.